A Study to Assess the Risk Factors for Coronary Artery Disease in Employees of Selected Educational Institutes of Navsari City, in a View to Prepare and Validate a SIM - Shivaji Savlajkar, Rohan (International Journal of Nursing Research, 2023)
Background: Coronary artery disease (CAD) significantly lowers quality of life. A complex and long-lasting inflammatory process that eventually results in fibrous atherosclerotic plaque can be accelerated or modified by risk factors. Up to 2030, this illness will continue to be the world’s most serious in terms of mortality, morbidity, disability, and economic loss. It is endemic in underdeveloped nations. By minimizing modifiable risk factors, the identification of risk variables offers a means for lowering the chance of developing CAD, and better treatment options are made thanks to more precise assessment of overall risk status. Methods: To determine the risk factors for CAD, a descriptive exploratory survey approach was utilized in this study. The investigation was carried out in two Navsari city educational institutions of choice. The sample size was 60 in total. Since the personnel were chosen at random using a lottery system, the study was based on a straightforward random sampling procedure. Results: Conclusions based on data analysis. Most instructors (62% of them) had a low risk, many (28% of them) a moderate risk, and none had a high risk of developing CAD. A typical percentage of the sample (43.33%) had an abnormal body mass index. Only 10% of male instructors have a normal waist-hip ratio (WHR), compared to 23.33% who have an unhealthy ratio. Maximum (35%) of females had abnormal and normal WHR (31.67%), respectively. Most teachers (75%) had normal cholesterol, while (25%) had levels above average. Conclusion: Years of experience and educational attainment were found to be significantly correlated with risk variables for CAD.